2013
DOI: 10.1017/s0317167100014694
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Inpatient Neurologic Disease in a Tropical African Hospital

Abstract: Abstract:Background:Neurologic disorders represent a major burden of disease globally and the spectrum ranges from noncommunicable disorders like stroke and neurodegenerative disorders to central nervous system infections.Objective:The purpose of the study is to assess the burden of neurological diseases in a tropical environment.Methods:A one year retrospective survey of neurological diseases seen at the University of Calabar Teaching Hospital, Nigeria, was evaluated using patients' medical record.Results:Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…The majority of published studies are from African countries; they include all age groups and report more acute NDs, including central nervous system infections [1, 2]. It was not the purpose of this study to define the prevalence of NDs among all inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of published studies are from African countries; they include all age groups and report more acute NDs, including central nervous system infections [1, 2]. It was not the purpose of this study to define the prevalence of NDs among all inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that clinical multimorbidity affects 99% of older adult women (≥65 years) and 97% of men [34], and these comorbidities increase the risks for adverse outcomes and the cost of healthcare [14, 35]. The mortality rate for older adult neurological inpatients (18%) was lower than that reported in African neurological inpatients, perhaps because those studies included more participants with severe infections such as HIV and brain tumors [1, 2]. However, compared with neurological inpatients aged 18–59 years, mortality among older adult patients was more frequent and there were differences in mortality and long LOS rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a pronounced need to describe the prevalence of neurological illness and identify predictors of mortality associated with these diagnoses in healthcare settings throughout Uganda and other sub-Saharan countries, electronic health record (EHR) systems, and hence, administrative data, are not widely available to aid in such endeavors. Several studies have analyzed inhospital mortality rates and associated factors in various sub-Saharan African countries, with no prior work analyzing in-hospital mortality among patients admitted to a neurology ward particularly within Uganda [9][10][11][12][13][14]. Understanding the prevalence and identifying high-risk causes of mortality is critical for healthcare providers and policy makers to prioritize public health, clinical, and quality improvement interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological disorders account for approximately 10% of all admissions in African rural hospitals [10][11][12]. However, the etiological spectrum has been hardly studied so far because of lack of diagnostic facilities [13].…”
Section: Introductionmentioning
confidence: 99%